2003
DOI: 10.1088/0964-1726/12/3/314
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and characterization of ionic polymer transducers employing non-precious metal electrodes

Abstract: Ionic polymer membranes are commonly used in fuel cell power generation, water electrolysis and desalinization, chlorine generation, and other niche applications. Since the early 1990s ionic polymer membranes have also shown promise as distributed electromechanical actuators and sensors. The cost of these materials is very high because of the expensive noble metals that are used as the electrodes in these applications, however. Currently, high cost of these devices has prevented them from experiencing widespre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 45 publications
0
41
0
1
Order By: Relevance
“…11 Bennet et al embedded precious and nonprecious metals via electroless plating into CNCs and have shown that both categories of metals can be used in forming CNC layers; yet precious metals, primarily gold or platinum, are advantageous as they eliminate the oxidation problem and do not require further processing steps such as a co-reduction process or deposition of an ultra-thin protective layer. 12 Use of aqueous electrolytes limits the operating voltage of actuators to values below the voltage of water hydrolysis. Bennett et al have shown that use of ionic liquids can eliminate this issue.…”
mentioning
confidence: 99%
“…11 Bennet et al embedded precious and nonprecious metals via electroless plating into CNCs and have shown that both categories of metals can be used in forming CNC layers; yet precious metals, primarily gold or platinum, are advantageous as they eliminate the oxidation problem and do not require further processing steps such as a co-reduction process or deposition of an ultra-thin protective layer. 12 Use of aqueous electrolytes limits the operating voltage of actuators to values below the voltage of water hydrolysis. Bennett et al have shown that use of ionic liquids can eliminate this issue.…”
mentioning
confidence: 99%
“…Each sample has Nafion r -117 as the base ionomer, sodium as the cation, and platinumgold electrodes. 19 The difference between the samples is that the first sample has water as the solvent, while the second sample has been solvated with the ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMI-Tf). While differing in dimensions, they do maintain a 4:1 length-to-width ratio (water: 8x2mm; EMI-Tf: 16x4mm).…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…45 Nevertheless, considering the high cost of noble metals some authors 46 developed a co-reduction process for plating ionic polymer materials that gives noble and non-noble metal alloy electrodes, with a resulting reduction in the consumption of expensive precious metals such as platinum and gold.…”
Section: Co-reductionmentioning
confidence: 99%
“…Though the concept of co-reduction is not a new one, [47][48][49] Bennett and Leo 46 developed a new process to reduce simultaneously a noble (Pt) and a non-noble metal (Cu) on the Nafion surface and to form an alloy sublayer consisting of two metal phases that appear to be homogeneously mixed.…”
Section: Co-reductionmentioning
confidence: 99%
See 1 more Smart Citation